Texting and Making Calls Whilst Driving: Can Hand-Free Car Kits and Smartphones Speaker Tones Come to the Rescue of Ghanaian Drivers? - Owusu, Acheampong; Abdurrahaman, Daha Tijjani; Bakare, Akeem Soladoye; Taana, Ivy Hawah (Technium Social Sciences Journal, 2021)
The safety of road users is paramount to every nation. As such, stringent measures are put in place to protect them. Such measures are multi-faceted which include legislation, policing, and technology. In spite of these, accidents still occur and are rampant on most developing economies’ roads, including Ghana. The purpose of this paper is to explore why Ghanaian drivers, despite the Road Traffic Regulations, 2012 L.I. 2180 Act continue to drive whilst holding their phones and texting/making/receiving calls. The study will also find out why such drivers are not using the Hands-Free Car Kit/Speaker Tones features in their phones that can let them make/receive calls without holding their phones. Again, the study investigated drivers’ attitude towards making/receiving calls and texting/reading text messages whilst driving through the lens of the theory of planed behaviour. With a survey data of 284 drivers from Accra, Ghana, and analyzed through partial least squares structural equation modeling (PLS-SEM), the results indicate that subjective norm and perceived behavioral control influence the actual behavioral intention towards texting and making phone calls whilst driving. Also, actual behavioral intention and perceived behavioral control influence behavior towards driving whilst texting and making calls. However, attitude towards behavior does not influence actual behavioral intention. The findings have provided insights into this phenomenon through scientific analysis which is lacking in the literature especially from a developing economy context. Other implications are also discussed.